Project Based Learning Model With Digital Wordwall Game Encourages Reading Skills Of Grade III Elementary School Students - Silviani, Novia Nanda; Rusnilawati, R (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the significant differences in students' reading ability after applying the Project Based Learning model with interactive media Wordwall game, compared to the Inquiry Learning Model with interactive video media Edpuzzle. Methodology: The research involved 46 students divided into two groups: a control group using the Inquiry Learning Model with Edpuzzle interactive video, and an experimental group using the Project Based Learning Model with Wordwall media. Data were collected through pre-test and post-test, and analyzed using the N-Gain value test. Validity and reliability tests were conducted on the instruments used. Results: The control group showed an N-Gain score of 0.42 (considered good enough), while the experimental group showed a higher score of 0.59, indicating a 59% improvement in reading ability (from 56% to 75%). Students in the experimental group demonstrated more enthusiasm and creativity, particularly in the process of product creation and interactive question exercises. Applications/Originality/Value: This research highlights the effectiveness of combining project-based learning with game-based media like Wordwall in enhancing reading skills. The interactive, product-oriented, and engaging learning process fosters not only better comprehension but also student motivation and creativity—making it a valuable approach for language learning environments.